2009
DOI: 10.1007/s00464-009-0475-6
|View full text |Cite
|
Sign up to set email alerts
|

The minimal clinically important difference in the Gastrointestinal Quality-of-Life Index after cholecystectomy

Abstract: This study showed that after patients had undergone cholecystectomy, the clinically significant mean changes in their scores on the GIQLI subscales for symptoms, emotions, physical functions, and social function were respectively 6.42, 6.86, 7.64, and 6.46 points. After patients have undergone cholecystectomy, the MCIDs for the GIQLI subscales can play an important role in interpretation of the scores, application of them in clinical practice, and verification of treatment effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 16 publications
1
19
0
2
Order By: Relevance
“…A previous study [4] of patients who had undergone cholecystectomy indicated that clinically significant mean changes in scores for the symptomatology, emotional impairment, physical impairment, and social impairment subscales of the GIQLI were 6.42, 6.86, 7.64, and 6.46 points, respectively. In the current study, the mean change in all GIQLI subscale scores for the LC patients 6 months after surgery exceeded these values, which indicated successful surgery.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A previous study [4] of patients who had undergone cholecystectomy indicated that clinically significant mean changes in scores for the symptomatology, emotional impairment, physical impairment, and social impairment subscales of the GIQLI were 6.42, 6.86, 7.64, and 6.46 points, respectively. In the current study, the mean change in all GIQLI subscale scores for the LC patients 6 months after surgery exceeded these values, which indicated successful surgery.…”
Section: Discussionmentioning
confidence: 97%
“…The GIQLI is recognized as a valid and reliable instrument for measuring HRQoL, especially for patients undergoing cholecystectomy [4][5][6]. Its 36 six items include symptomatology (19 items), emotional impairment (5 items), physical impairment (7 items), social impairment (4 items), and the effects of medical treatment (1 item).…”
Section: Instruments and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with symptomatic cholelithiasis or cholecystitis, complication rates and mortality rates are lower and hospital stays are shorter after LC than after OC [13][14][15]. Compared to OC, LC is also associated with substantially higher patient-reported HRQoL scores at 3-6 months postoperatively [13,14].…”
Section: Introductionmentioning
confidence: 96%
“…Although the impact of response shift on selfreported HRQoL outcomes has not been studied extensively in cholecystectomy patients, the literature does indicate that response shift occurs in LC patients. Shi et al [14] reported that, in patients who had undergone cholecystectomy, the minimal clinically important differences (MCIDs) in scores for the symptoms, emotions, physical functions, and social function subscales of the GIQLI were 6.42, 6.86, 7.64, and 6.46 points, respectively. They also found that the effect sizes of four anchors in the ''somewhat better'' group (0.38-0.49) exceeded those of the ''same'' group (0.25-0.38).…”
Section: Introductionmentioning
confidence: 98%